Calidad de vida de pacientes renales crónicos en tratamiento con hemodiálisis en el hospital general Isidro Ayora Loja - Guerra Jiménez, Roosevelt Washington (2022)
Chronic kidney disease is defined as the presence of alterations in renal structure or function for at least three months, with implications for the health of the affected person. The purpose of this research was to determine the quality of life of chronic renal patients undergoing hemodialysis treatment at the Isidro Ayora Loja General Hospital, through the sociodemographic characterization of the study population, measurement of quality of life and determination of the most affected area of their daily life through the use of the quality of life scale developed by the World Health Organization, WHO - QOL BREF. A descriptive, cross-sectional, non-experimental study was carried out at the Isidro Ayora General Hospital in the city of Loja, from September to December 2020. The processing of the data collected was carried out in the Excel program, and descriptive statistics were used for the analysis and interpretation of the information. A sample of 66 patients with chronic renal failure undergoing hemodialysis treatment was taken, of which 44 were male, 66.67%, while the remaining 33.33% were female patients. In conclusion, it is important to point out that chronic kidney disease entails different physical and social changes for patients, which are directly related to the patients' perception of their quality of life